Comercio exterior de industrias de la madera en los países de la UE : análisis del período 1961-1995 y modelización econométrica - Iglesias Casal, Ana (1998)
"This study analyses the European forest industries during the period 1961-1995. First of all, we have analysed the different structures of the European sawmilling and wood-based panels industries. In this conection, it should be noted that small and medium-sized enterprises in the sawmilling industry and large enterprises in wood based panels industry are the predominant structures. The differences also are important in others items as productivity and technological improvements. On the other hand, econometric models of sawnwood and wood-based panel markets in European Union have been estimated from 1970 to 1993. In this context it was analysed the domestic demand and supply, as well as the exports and imports, with the objective of deriving a model to provide consistent long-range projections of trends in forest products consumption and production. Finally, we made a forecast evaluation, which consists in the comparison of the forecasted values of the export equation with VAR, error correction models (ECM) and structural models."